Leucoencefalomalacia y bocio en un feto equino en el noroeste argentino - Colque Caro, Luis Adrián; Olmos, Leandro Hipolito; Aguirre Castro, Laura Sabrina; Avellaneda Cáceres, Agustín; Sanz, I.; Micheloud, Juan Francisco (EEA Balcarce, INTA, 2022)
Poster